The effect of parenting style and genetic personality on children character development - Masduki Asbari; Wakhida Nurhayati; Agus Purwanto (Graduate School, Universitas Negeri Yogyakarta, 2019)
Character building is very important to become a key for educational mainstream in Indonesia, either in a formal, non-formal, and informal setting. Several factors influence character building in children, namely parenting style and genetic personality. The purpose of this research is to identify the influence of parenting style and genetic personality to children’s character development. This research is a correlational study using a survey and quantitative method. The population in this study were parents of students in Aya Sophia Foundation Islamic School. Data collection was carried out by simple random sampling to a population of 1,243 students' parents using an electronic questionnaire. The returned and valid questionnaire results were 398 samples. The data collection technique used was a questionnaire with a Likert scale. The instrument of this study is a modification from the Parenting Style Questionnaire (PSQ) of Robinson et al. and Roman et al. To measure the genetic personality, the instrument was adapted from STIFIn Personality Concept. Another instrument used to measure children's character development is an adaptation from Poniman et. al. The analysis in this study used SEM (Structural Equation Model) with SmartPLS version 3.0 as a statistic tool. The result of this study shows that parenting style and genetic personality have a positive influence and significantly contribute to children's character building.